2005
DOI: 10.1002/nme.1436
|View full text |Cite
|
Sign up to set email alerts
|

Generalized nodes and high-performance elements

Abstract: SUMMARYThe paper concerns the development of robust and high accuracy finite elements with only corner nodes using a partition-of-unity-based finite-element approximation. Construction of the partition-ofunity-based approximation is accomplished by a physically defined local function of displacements. A 4-node quadratic tetrahedral element and a 3-node quadratic triangular element are developed. Eigenvalue analysis shows that linear dependencies in the partition-of-unity-based finite-element approximation cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 40 publications
0
59
0
Order By: Relevance
“…Duarte et al [14] have shown that quadratic GFEM elements with shape functions (7) are more computationally efficient than classical TET10 elements. These element types are also studied in [60,61]. However, since in Abaqus we are limited to classical finite elements, we adopt TET4 or TET10 elements for all global meshes.…”
Section: Elements Types In Global and Local Discretizationsmentioning
confidence: 99%
“…Duarte et al [14] have shown that quadratic GFEM elements with shape functions (7) are more computationally efficient than classical TET10 elements. These element types are also studied in [60,61]. However, since in Abaqus we are limited to classical finite elements, we adopt TET4 or TET10 elements for all global meshes.…”
Section: Elements Types In Global and Local Discretizationsmentioning
confidence: 99%
“…A clustered POU function is identically equal to one over part of its support as illustrated in Figures 4 and 5. This property can be used to eliminate the well known linear dependence of generalized finite element shape functions [37,56]. The multigrid method is not directly applicable to the linear system when the stiffness matrix is positive semi-definite [28].…”
Section: Gfem Shape Functions With Clustered Poumentioning
confidence: 97%
“…The displacements that are described by the drilling and strain DOFs are superimposed on the ordinary ones ( u , v ) that are the translational DOFs. In elastic stress problems, GNT3 is known to be as accurate as quadratic element (12) . In addition, GNT3 can easily be extended to the case of three-dimensional tetrahedral finite element.…”
Section: Generalized Finite Element With Drilling and Strain Dofs (Gnt3)mentioning
confidence: 99%
“…In addition, GNT3 can easily be extended to the case of three-dimensional tetrahedral finite element. According to Tian and Yagawa (12) the displacements of GNT3 are written to be: Here, the superscript I indicates node (1, 2 or 3) of triangular element. …”
Section: Generalized Finite Element With Drilling and Strain Dofs (Gnt3)mentioning
confidence: 99%
See 1 more Smart Citation